World Tendences of civil aviation development and the enlargement of the Lithuanian civil aviation - Butkevičius, Jonas; Jarašūnienė, Aldona (Transport, 2006)
The article deals with global trends in civil aviation, such as: liberalisation of aviation market, globalisation of airlines, privatisation of airlines and invasion of low cost airlines into the market. Also the influence of these trends on the Lithuanian civil aviation activities has been defined. The Lithuanian civil aviation activities have been analysed: activities of international airports, passenger and cargo carriers, passenger routes and passenger flows, transportation market and airplane fleet. The problems of the Lithuanian civil aviation activities have been identified and suggestions for the development of the Lithuanian civil aviation activities have been proposed.First Published Online: 27 Oct 2010